Influence of Mo–Nb–Ti Additions and Peak Annealing Temperature on the Microstructure and Mechanical Properties of Low Alloy Steels After Ultrafast Heating Process - Castro-Cerda, F; Hernandez-Duran, E (Elsevier Ltd, 2021)
The influence of the heating rates from 10 to 1000 °C/s and annealing temperatures on the microstructure and mechanical properties of two 0.2%C, 1.9%Mn, 1.4%Si cold-rolled steels with and without the addition of carbide-forming elements (Mo, Nb, and Ti) have been investigated. Results show that the increase of the heating rate above 100 °C/s refines the parent austenitic grains in both alloys. The increment of the heating rate led to carbon heterogeneities in the austenite, which after subsequent cooling promoted the formation of a complex mixture of fine-grained constituents. As expected, at the lower heating rates the presence of Nb and Ti-rich carbides and carbonitrides controls the austenite grain growth during the annealing treatment. The tensile test results reveal that high heating rates do not have a significant influence on the tensile strength of the alloy with carbide-forming elements. On the other hand, both the ultimate tensile strength (UTS) and total elongation of the alloy without carbide-forming elements decrease, due to the formation of bands of ferrite and high carbon martensite. However, samples treated at heating rates above 100 °C/s show a combination of UTS in the range of 1400–1600 MPa, and 12–18% of total elongation. The results suggest that the microstructure heterogeneity obtained after high heating rates, especially the ferrite content, has the major effect on the mechanical behavior of the studied steels. © 2021 Elsevier B.V.